Measurement of the Brain Volume/Liver Volume Ratio by Three‐Dimensional MRI in Appropriate‐for‐Gestational Age Fetuses and Those With Fetal Growth Restriction. Issue 6 (21st June 2021) - Li, Kui; Yan, Guohui; Zheng, Weizeng; Sun, Jin; Zou, Yu
Abstract : Background: Fetal growth restriction (FGR) is associated with a high fetal brain volume/liver volume (FBV/FLV) ratio. Ultrasound may not always be reliable, which has prompted further investigation of MRI techniques. Purpose: To determine the relationship between FBV/FLV ratio, as measured by MRI, and gestational age (GA) in normal fetuses and those with FGR. Study Type: Retrospective. Population: One hundred and forty seven singleton pregnancies including 105 appropriate‐for‐gestational age (AGA) fetuses and 42 FGR fetuses. Field Strength/Sequence: Three‐dimensional fast imaging employing steady‐state acquisition at 1.5 T. Assessment: The FBV and FLV were measured by three radiologists. The inter‐ and intraobserver agreements, the correlation between FBV/FLV ratio, and advancing GA were evaluated; the diagnostic value of FBV/FLV ratio was evaluated and compared with head circumference/abdominal circumference (HC/AC) ratio measured by ultrasound. Statistical Tests: Intraclass correlation coefficient (ICC) was used to determine inter‐ and intraobserver agreements. Regression analysis was used to assess the correlation between FBV/FLV ratio and advancing GA. The diagnostic value of the FBV/FLV ratio was examined by the area under the receiver operating characteristic (ROC) curve. Results: The inter‐ and intraobserver agreements were excellent with an interobserver ICC of 0.984 and intra‐observer ICCs of 0.989, 0.994, and 0.995. The FBV/FLV ratio in AGA fetuses decreased significantly with advancing GA (Pearson correlation coefficient = −0.844). The FBV/FLV ratio in FGR fetuses was significantly higher than that in AGA fetuses. To identify fetuses at high risk for FGR using the FBV/FLV ratio, the area under the ROC curve was 0.978, with an optimal cut‐off value of 4.10. The sensitivity of FBV/FLV ratio in identifying FGR was significantly higher than that of HC/AC ratio (0.929 vs. 0.529). Data Conclusion: An inverse correlation exists between FBV/FLV ratio and advancing GA in normal fetuses. A high FBV/FLV ratio may be used to ascertain fetuses at high risk for FGR. Level of Evidence : 3 Technical Efficacy Stage : 3